Economic Resilience of Rural Families of the Deaf: Strategies for Coping with Social Exclusion and Accessibility - Qodriyati, Tri 'Ulya; Puspitasari, Savira Widya; Widyaswari, Monica; Purnamasari, Ica Salim, Tisya Fajriatus; Islami, Zahwa (Universitas Negeri Padang, 2025)
This study aims to identify the economic resilience strategies of visually impaired families in rural Grobogan Regency, Indonesia, who face the challenges of social exclusion and limited accessibility. The method used is a qualitative approach of a case study wi th a purposive sample consisting of 10 visually impaired families who are actively involved in daily economic activities. Data was collected through in-depth interviews, participatory observations, and documentation. The results of the study show that social stigma against people with disabilities is the main obstacle to their participation in economic and social activities. Discrimination in employment opportunities and limited access to education and public services also exacerbate their economic resilience. Nonetheless, rural blind families show resilience through adaptation strategies, such as working in the informal sector, opening home businesses, and leveraging social support from extended families and communities. This research provides new insights into the importance of creating an inclusive social environment and policies that support accessibility for people with disabilities, in order to improve their economic resilience. These findings can also serve as a reference for the government and the community in designing more inclusive empowerment policies.